MONITORING DAN ANALISIS IP CAMERA PADA JARINGAN INTERNET - ., Ajie Pambudhi (Jurnal Teknik Elektro Universitas Tanjungpura, 2017)
IP Camera is one type of surveillance camera system that allows users to monitor a room or a specific place. The recording of the camera is stored on an NVR (Network Video Recorder) device and to display the recording  of the camera using a PC monitor. For  monitoring, usually using a local network, this is certainly not effective  if the room is abandoned  by the owner. In this final project configure IP Camera  to be accessed through internet network and evaluate QoS internet network. From the research results can be concluded that IP camera monitoring can be done through internet network. The average internet access speed measurement at the Faculty of Engineering Tanjungpura University for download and upload each valued at 10.81 Mbps and 6.39 Mbps. The delay result is 186.50 ms. Compared to the standardized network performance based on TIPHON, it is included in the "good" category. Meanwhile, when compared with the standardization  of network performance based on ITU-T, then included in either category. The result of packet loss is 1%. Compared to the standardized network performance based on TIPHON, it belongs to the "very good" category. While compared with the standardization  of network performance based on ITU-T, it is included in the "good"  category.  The throughput  result  is  46.82  Kbps. Compared  to  the  standardized  network performance based on TIPHON, it belongs to the "bad" category. Factors  that cause the decline in network quality is the unstable internet network caused by the large number of internet users in the Faculty of Engineering Tanjungpura University.   Key words : Monitoring, IP Camera, QoS